A systematic review of the human health and social well-being outcomes of green infrastructure for stormwater and flood management. (15th September 2019) - Venkataramanan, Vidya; Packman, Aaron I.; Peters, Daniel R.; Lopez, Denise; McCuskey, David J.; McDonald, Robert I.; Miller, William M.; Young, Sera L.
Abstract: Background: The increase in frequency and intensity of urban flooding is a global challenge. Flooding directly impacts residents of industrialized cities with aging combined sewer systems, as well as cities with less centralized infrastructure to manage stormwater, fecal sludge, and wastewater. Green infrastructure is growing in popularity as a sustainable strategy to mimic nature-based flood management. Although its technical performance has been extensively studied, little is known about the effects of green stormwater infrastructure on human health and social well-being. Methods: We conducted a multidisciplinary systematic review of peer-reviewed and gray literature on the effects of green infrastructure for stormwater and flood management on individuals', households', and communities' a) physical health; b) mental health; c) economic well-being; and d) flood resilience and social acceptance of green infrastructure. We systematically searched databases such as PubMed, Web of Science, and Scopus; the first 300 results in Google Scholar; and websites of key organizations including the United States Environmental Protection Agency. Study quality and strength of evidence was assessed for included studies, and descriptive data were extracted for a narrative summary. Results: Out of 21, 213 initial results, only 18 studies reported health or social well-being outcomes. Seven of these studies used primary data, and none allowed for causal inference. No studies connected green infrastructure for stormwater and flood management to mental or physical health outcomes. Thirteen studies were identified on economic outcomes, largely reporting a positive association between green infrastructure and property values. Five studies assessed changes in perceptions about green infrastructure, but with mixed results. Nearly half of all included studies were from Portland, Oregon. Conclusions: This global systematic review highlights the minimal evidence on human health and social well-being relating to green infrastructure for stormwater and flood management. To enable scale-up of this type of infrastructure to reduce flooding and improve ecological and human well-being, widespread acceptance of green infrastructure will be essential. Policymakers and planners need evidence on the full range of benefits from different contexts to enable financing and implementation of instfrastructure options, especially in highly urbanized, flood-prone settings around the world. Therefore, experts in social science, public health, and program evaluation must be integrated into interdisciplinary green infrastructure research to better relate infrastructure design to tangible human outcomes. Highlights: No studies were found on human health impacts of green stormwater infrastructure Most economic studies focused on property value and green stormwater infrastructure Social and health research is key to understand and scale‐up green infrastructure Rigorous program evaluation will strengthen the evidence base for policymakers